The moderating role of coping strategies in athletic coaches` psychological well-being in response to negative emotions - Lee, Y. H.; Cho, H. (International Journal of Sports Science & Coaching, 2023)
Negative emotions are known risk factors for physical health, psychological distress (e.g. hopelessness and feeling worthless), and mood disorders (e.g. depression and anxiety). Thus, it is important for athletic coaches, one of the most stressful occupations, to understand how to cope with their negative emotions. This study aimed to examine the moderating roles of four different coping strategies (emotion-focused, problem-focused, proactive, and emotive suppression) on the relationship between negative emotions and psychological well-being. Online survey data were collected from 162 athletic head coaches working in NCAA Division I through questionnaires that assessed the proposed variables. The results reported that proactive coping strategy and emotive suppression strategy negatively and significantly moderated the negative emotional-psychological well-being relationship. The findings of this study contribute to understanding the coping strategies that should be avoided in response to negative emotions among coaches. The results also highlight the need to consider adopting existing proactive coping intervention programs for coaches.